Strategi Corporate Social Responsibility (CSR) Dalam Program Alokasi “Bedah Rumah” Untuk Meningkatkan Citra Pada Perusahaan PT Semen Tonasa Pangkep - Asmi Izzaty, Andi; Ahdan, Ahdan; Muttaqin , Andi (UNIVERSITAS MUSLIM INDONESIA, 2022)
The purpose of this research is determine the Corporate Social Responsibility (CSR) strategy in the home renovation allocation program to improve the image of the company PT Semen Tonasa Pangkep, and determine the implementation of CSR to improve the image of a company. The method used in this research is descriptive qualitative. Using Interview, Observation, and Documentation methods. This research lasted for approximately one month located at PT Semen Tonasa Pangkep. The research informants from Corporate Social Responsibility (CSR) unit and staff of PT Semen Tonasa Pangkep and also the people who received assistance from the house renovation program. The results of this study indicate that the Corporate Social Responsibility (CSR) strategy in the home renovation program is to improve the image of the PT Semen Tonasa Pangkep company, namely using Bottom Up through LCO or village forums by providing proposals to the company to be approved by the company. And the impact of the implementation of the Corporate Social Responsibility (CSR) program is a positive impact on the companys image through the community.